PENGARUH DAN PERAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PERUSAHAAN TERHADAP KESEJAHTERAAN EKONOMI MASYARAKAT : Corporate Social Responsibility Perusahaan Terhadap Kesejahteraan Ekonomi Masyarakat - Ariani, Taufiqoh Bina; Setiady, Tri; Abas, Muhamad; Budi Santoso, Imam (Mendapo: Journal of Administrative Law, 2023)
The work of the Corporate Social Obligation organization is required in the financial success of the local region in order to aid the community's economy, which combines diverse points of view. so that business in society is not perceived as a danger to the environment and solely has an interest in obtaining profit. The effect of the Corporate Social Responsibility program must be accountable in strengthening the community's economy, according to Government Regulation Number 47 of 2012 concerning Social and Environmental Responsibility of Limited Liability Companies. The author poses the following questions: "How does the Company's Corporate Social Responsibility Influence in Improving Community Welfare?" and "What is the Role of Company Corporate Social Responsibility as Corporate Responsibility in Building the Community's Economy?" This is an issue that must be addressed. The research approach used in this study is normative writing with qualitative methodologies, with some normative law concerns. The use of a company's corporate social responsibility idea not only improves the company's reputation, but it must also be able to deliver advantages to the nation's people across all sectors and the economy.